CATHOLIC CHURCH AT THE CROSSROADS : THE POLISH CASE (Religious dialogue and cooperation, 2021)
Poland and Poles are and have always been stronglyattached to Catholicism. In the national tradition, we defineourselves as the „rampart (defensive wall) of Christianity,” securingEurope from the dominance of Islam (the Ottoman Empire).During the partition period, confession was the determinant of beinga Pole. The Catholic Church was perceived as a mainstay of Polishnational identity, the only institution where Polish language couldbe used. The church was similarly treated during the communistperiod, as well - it was the mainstay of patriotism, helped the illegalopposition, organized help for the persecuted.No wonder that in the traditional social narrative the church wasand still is treated as a national institution, and confession as animportant (even dominant) component of national identity. Beinga Catholic was a source of pride, after all we had the Polish Pope.Why, then, the thesis that it is at a crossroads? I assume that itis determined by the present conditions and processes that takeplace on a global scale. Poland, which has been surprised by fullchurches, currently has the largest decline in dominicantes andcommunicantes in the whole world, despite the fact that most ofthe Poles declare themselves to be Catholics.What decides about it? In my opinion, approaching Catholicism andits practices as a shelf in a supermarket - one chooses what is usefulto him at a given moment. There is also another aspect of Churchactivity in Poland - political activity that expresses support for thoseparties that appeal to nationalism, traditional narrative to therole of the Church in the past and influencing the creation of thelaw, that religious dogmas/norms (Catholic) should be respected.This testifies to the weakness of the evangelizing and educationalmission of the Church.Keywords: Catholic
Keywords: Catholic Church; evangelization; tradition; nationalism; politics